Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Dinas Kominfo Kota Bima: The Influence Of Work Environment And Organizational Culture On Employee Performance At The Bima City Communications And Information Service - Susilo, Susilo; Badar, Muhammad; Yusuf, Muhammad (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the influence of the work environment and organizational culture on employee performance at the Bima City Communication and Information Service. The research instrument used a Likert scale questionnaire. The sample in this study was 46 respondents with a purposive sampling technique. Data collection techniques used observation, questionnaires, and literature studies. Analysis using multiple linear regression. The results of the study indicate that partially only organizational culture has a significant influence on employee performance, but simultaneously the work environment and organizational culture have a significant influence on employee performance at the Bima City Communication and Information Service.